Peran Kebijakan Perlindungan Hutan dalam Mengurangi Dampak Kebakaran Hutan terhadap Kesehatan di Provinsi Kalimantan Tengah dan Riau - Arianti, Tanti; Wulandari, Christine; Bakri, Samsul; Sukohar, Asep; Noviani, Erina; Hardito, Joni (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study aims to analyze forest protection policies in mitigating the health impacts of forest fires, with a particular focus on the provinces of Central Kalimantan and Riau. The method used is a literature review, involving the analysis of legal regulations, regional policy documents, and relevant academic journals. Although Indonesia has a relatively strong legal framework, policy implementation faces significant challenges, including limited resources and widespread dependence on land-burning practices by both local communities and corporations. Health impacts such as acute respiratory infections (ARI) and chronic respiratory problems continue to rise alongside the frequency of forest fires. Based on data from the Ministry of Environment and Forestry, in 2019 Central Kalimantan contributed 134,227 hectares and Riau 75,871 hectares to the national total of 1.64 million hectares of burned area. Therefore, a more integrated, prevention-oriented policy approach involving community participation and early detection technologies is urgently needed